Kirsten eaudiobook An american girl. - Beeler Shaw, Janet (American Girl: Kirsten., 2011)
The American Girl brand is synonymous with wholesome, empowering tales about young women growing up in America, even as the country grows, too. Each girl's story documents with unsurpassed charm and wit the people, places, and events she witnesses. Taking place in 1854, Kirsten's stories follow the young Swedish immigrant and her family as they attempt to start a new life on a farm in frontier Minnesota. This collection includes: Meet Kirsten, Kirsten Learns a Lesson, Kirsten's Surprise, Happy Birthday, Kirsten!, Kirsten Saves the Day, and Changes for Kirsten.